Eroded topography in Proterozoic Basement: the case of Capiá river watershed, Semi‐arid Northeastern Brazil - Panta, Genisson; Nascimento, João Paulo da Hora; Monteiro, Kleython de Araújo (Revista Brasileira de Geomorfologia, 2022)
: It is a consensus that the semi-arid depressions created in Atlantic Proterozoic Shield underwent intense denudational processes, especially during the Cenozoic. However, there are still no studies on quantifying and spatializing the fluvial incision for the Southern Sertaneja Depression, low course of the São Francisco river. Then, this study sought to quantify and spatialize the fluvial incision over the Proterozoic basement in the Capiá river basin through the integration of geoprocessing and geostatistical techniques (ordinary kriging), based on a Digital Elevation Model. Correlations were drawn between lithological resistance, basement structures and geomorphological aspects. More than half of the analyzed watershed mass has already been removed by denudational processes and the minimum bulk erosion per corresponding area is in contrast with other regions of the planet. The reconstitution of the topography allowed the delimitation of two large morphostructural compartments in the basin. Finally, apatite fission track data from studies already published in the study area were presented.